Relationship of hippocampal theta and gamma oscillations to potentiation of synaptic transmission - Bikbaev, Arthur; Manahan-Vaughan, Denise (Frontiers in Neuroscience, 2008)
In the hippocampus in vivo, both synaptic plasticity and network activity are closely interdependent. We have found that immediately after an attempt to induce long-term potentiation (LTP), changes in theta (5-10 Hz) and gamma (30-100 Hz) activity correlate tightly with the occurrence of LTP, suggesting that tetanisation-driven activation of sensory inputs synchronises the activity of granule cells and interneurons, and thus, facilitates the encoding of acquired stimuli. This results in increase of theta and gamma power, and elevates the probability that afferent stimuli both coincide with the peak of theta cycle and reach their post-synaptic target within the gamma time-window (of 10-30 ms). Both these mechanisms can effectively shift the direction, of tetanisation-induced changes in synaptic weight, towards potentiation and induction of LTP. Here, we discuss our findings in the context of possible mechanisms that link theta and gamma oscillations with LTP induction, as well as their role in information processing and formation of memories.